The Local Wisdom-Based STEM Worksheet to Enhance the Conceptual Understanding of Pre-service Physics Teacher - Indri Sari Utami; Mudmainah Vitasari; Indah Langitasari; Iwan Sugihartono; Yuli Rahmawati (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2020)
The STEM (Science, Technology, Engineering, Mathematics) approach plays an important role in developing students’ abilities. The ability to combine science, technology, technical expertise, and mathematics is a tool that can help human life can be created. Of course, the application of STEM needs to be assisted by teaching materials in the form of Worksheets. With the STEM implementation worksheet, it can be more easily implemented without the lecturer having to explain each material fully. Because it must be students who develop their abilities. Following constructivist learning theory, by constructing one’s knowledge, the knowledge will be stored longer in memory. The ability in STEM is also very important in the current era of globalization. With the rapid advancement of technology, each individual is required to continue to innovate in developing a technology product. The basic ability that students need to have in learning basic physics is to understand a concept. A good understanding of the concept will be very supportive when prospective teachers later teach. It is expected that through the application of STEM, students are directly involved actively in designing and making products, and understanding concepts can be better. Products made by students must be really needed so that they can be used every day. It is better if the product utilizes local wisdom that is around the student environment. The product to be made is to convert the abundant solar thermal energy in Serang into a heater that can be used for cooking. It is a renewable energy because the heat in Serang is sweltering up to 32° C, so it can be used more than just drying. Based on these needs, mak a worksheet STEM based on local wisdom needs to be applied in learning. The results of this study stated that the local wisdom-based STEM worksheet on temperature and heat material for Physics teacher candidates was developed as a learning medium to increase students’ interest and understanding through independent learning.